2017
DOI: 10.24200/sci.2017.20019
|View full text |Cite
|
Sign up to set email alerts
|

An effective approach for structural damage localization in flexural members based on generalized S-transform

Abstract: This paper presents a method for structural damage localization based on signal processing using generalized S-transform (S GS ). The S-transform is the combinations of the properties of the short-time Fourier transform (STFT) and wavelet transform (WT) that has been developed over the last few years in an attempt to overcome inherent limitations of the wavelet and short time Fourier transform in Time-Frequency representation of non-stationary signals. The generalized type of this transform is the S GS -transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The key point is that there are many effective damage detection techniques in the literature, which are suitable for rectangular structures in the Cartesian coordinates [7][8][9][10][11][12]. Most of these techniques are not directly applicable to circular structures, and it is also very difficult to extend them to the polar coordinates.…”
Section: Introductionmentioning
confidence: 99%
“…The key point is that there are many effective damage detection techniques in the literature, which are suitable for rectangular structures in the Cartesian coordinates [7][8][9][10][11][12]. Most of these techniques are not directly applicable to circular structures, and it is also very difficult to extend them to the polar coordinates.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results showed that the proposed method had high accuracy. Tehrani [22] utilized an artificial intelligence method based on fast Fourier transform (FFT) to recognize structural damage degree. The results showed that FFT was suitable for nonstationary vibration signals.…”
Section: Introductionmentioning
confidence: 99%
“…In doing so, higher frequency resolutions are brought, and a uniform resolution for all scales is provided [15]. However, WT and SFFT have limitations in Time-Frequency representation of non-stationary signals [16]. Huang et al [17,18] rstly developed a new method{Hilbert Huang Transformation (HHT){in order to analyze both nonlinear and non-stationary signals.…”
Section: Introductionmentioning
confidence: 99%